Menulis Kreatif: Implementasi Pendekatan Kontekstual dalam Pembelajaran Bahasa Indonesia - Kamila (Faculty of Tarbiyah and Teacher Training, 2024)
The 21st-century educational learning approach is student-centered and created to meet the demands of the modern classroom. One of the things expected in 21st-century education is for students to understand writing literacy. However, there are still many students who cannot write, especially those who can write creative essays. The Contextual Teaching and Learning (CTL) approach can be used so students can write creative essays. This research aims to describe implementing a contextual approach to improve the quality of creative writing in elementary school or MI students. The research design used is Classroom Action Research, which uses a qualitative approach through four stages, namely: (1) planning, (2) implementation, (3) observation, and (4) reflection. Data collection techniques include direct field tests, observations, and documentation. The results of the research show that there is an increase in the quality of students' creative writing skills in learning Indonesian for elementary/MI students, with an average of 80% or 15% of students getting a learning process ability score in Indonesian writing or composing exercises in the very good category. 55% of students received an average score of 80, and the lowest score was 75. The average class score was 74, with a class ability level of 48.15%. This means that students can already write essays well and correctly.